The role of an internal nasal dilator in athletes - Gelardi, Matteo; Porro, Giuseppe; Accettura, Domenico; Quaranta, Vitaliano Nicola; Quaranta, Nicola; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2019)
The nasal valve area has the minimal cross-sectional area of the upper airways. Nasal dilators have been found able to improve sport performance in athletes. The aim of this study was to investigate whether the use an internal nasal dilator may be able to affect respiratory pattern in a group of athletes. The use of internal nasal dilator induced a significant reduction of fatigue perception (p=0.000) and was optimally accepted. In conclusion, the present study demonstrates that Nas-air® is an internal nasal dilator able to reduce the fatigue perception and is preferred to external nasal dilator.